A New Cheap and Efficient Single-Grain Shatter Tester for Use in Rice Breeding - Lamo, Jimmy; Tongoona, Pangirayi; Okori, Patrick; Derera, John; Hendricks, Roelof; Laing, Mark (Crop science, 2011)
Grain shattering, also called grain shedding, is the relative ease with which rice (Oryza sativa L.) seed is dislodged from the pedicel at maturity. Several qualitative methods have been used to assess grain shattering and they tend to underestimate yield loss. Equipments available for quantitative assessment of grain shattering are mostly laboratory based. However, a recently developed prototype in Japan for fi eldwork can be used, but the cost is prohibitive. An improved grain-shattering tester that uses a hand-held device has been developed and reported here. It is an improvement over the stationary laboratory device. It has the following modifi cations: a crocodile clip instead of a bench clamp and a helical spring for testing tensile material instead of tension gauge. The new device is affordable, handy for fi eldwork, and effective for large experimental trials. This equipment was designed and developed at the University of KwaZulu-Natal (UKZN) mechanical workshop (Pietmeritzburg, South Africa). Its effi ciency was tested at the National Crops Resources Research Institute (NaCRRI) at Namulonge, Uganda. The effi ciency was tested by fi rst estimating yield loss in selected test plants using a method that involves shaking panicles. This fi nding was compared with the minimum force required to dislodge the grains using this new device and a high correspondence of R2 = 99.9% was found. This new equipment has therefore been recommended for fi eld assessment of grain shattering.
Keywords: Cheap; Single-Grain Shatter Tester; Rice Breeding